Stimuli-responsive luminescent supramolecular assemblies and co-assemblies through orthogonal dipole–dipole interactions and halogen bonding. Issue 35 (23rd August 2021) - Jamadar, Akshoy; Singh, Ajeet Kumar; Roy, Lisa; Das, Anindita
Abstract : Naphthalene monoimide derivatives produced distinct stimuli-responsive luminescent nanostructures through orthogonal dipole–dipole interactions and halogen bonding (XB) with diverse graftable XB donors and acceptors in organic solvents. Abstract : This article reports π-chromophore assemblies from three structurally related dipolar naphthalene monoimide (NMI) luminogens (M1, M2 and M3 ) through underexplored orthogonal dipole–dipole interactions and halogen bonding. Single crystal structure analysis together with computational studies emphasized the predominance of dipole–dipole interaction mediated antiparallel π-stacking in the crystalline state, which could be tuned by varying the substituents at the imide- and 4-position of the aromatic ring. Interestingly, the self-assembly in 20% dioxane/methylcyclohexane revealed a different mode of supramolecular interactions. M2, equipped with both a halogen bond (XB) donor (bromine atom) and acceptor (pyridyl group), produced blue emitting 1D nanowires via orthogonal N⋯Br halogen bonding and antiparallel π-stacking. M1 and M3, lacking either the XB donor or acceptor, generated analogous spherical nanoparticles in the absence of extended N⋯Br halogen bonding. However, both M1 and M3 could act as chain stoppers for M2 and regulate its morphology via alternate halogen bonding and π-stacking with M2 in the co-assembled state. By varying the feed ratio between M1 and M2, the co-assembly properties could be tuned. At a lower fraction of M1 (∼1%), nanowires were predominant, while with increasing M1 fraction (>1%), the coexistence of nanowires and spherical particles was noticed. Above 10%, only spherical particles were visualized. Computational studies fully supported the experimental findings and revealed the synchronized operation of multiple noncovalent forces in stabilizing these co-assembled structures under different conditions. Furthermore, the presence of the XB-accepting pyridyl moiety in M1 and M2 rendered the possibility of engineering their supramolecular assemblies and photophysical properties by halogen bonding with an externally added cholesterol-based XB donor (Chol-D ). As a result, morphological switching of M1 and M2 occurred in the presence of Chol-D, from green emitting spherical particles to nanotapes and blue emitting nanowires to 2D nanosheets, respectively. The acid-labile pyridyl moiety bestows additional pH-responsive disassembly properties to these luminescent nanostructures.